The effectiveness of postpartum exercise to increase the quality of life score of postpartum mothers. - Inge Anggi Anggarini (Jurnal Delima Harapan, 2021)
Pregnancy, childbirth and postpartum are dramatic episodes of the biological conditions, psychological changes and adaptations of a woman who has experienced them. Complex physical and emotional changes make a mother-to-be need adaptation to lifestyle adjustments related to pregnancy, childbirth and the postpartum period. The adjustment process may work but some may not work so that the mother-to-be can experience psychological disorders with various symptoms or syndromes. There are several efforts that can be made to improve the quality of life for postpartum mothers, including postpartum exercise. The aims: to analyze the effectiveness of postpartum exercise to increase the quality of life score of postpartum mothers. The Method: This study was a quasi-experimental study with a pre-posttest control group design. Sampling taken by consecutive sampling. Results: The results showed that there were significant mean differences in the quality of life scores between the treatment group and the control group (p <0.05). Conclusion: The results of this study are expected to make a positive contribution to the science of midwifery as a non-pharmacological effort to improve the quality of life for postpartum mothers and to support government efforts to reduce maternal mortality and morbidity.